-4(x+2)+8=2(x-1)-7x+15

Simple and best practice solution for -4(x+2)+8=2(x-1)-7x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+2)+8=2(x-1)-7x+15 equation:


Simplifying
-4(x + 2) + 8 = 2(x + -1) + -7x + 15

Reorder the terms:
-4(2 + x) + 8 = 2(x + -1) + -7x + 15
(2 * -4 + x * -4) + 8 = 2(x + -1) + -7x + 15
(-8 + -4x) + 8 = 2(x + -1) + -7x + 15

Reorder the terms:
-8 + 8 + -4x = 2(x + -1) + -7x + 15

Combine like terms: -8 + 8 = 0
0 + -4x = 2(x + -1) + -7x + 15
-4x = 2(x + -1) + -7x + 15

Reorder the terms:
-4x = 2(-1 + x) + -7x + 15
-4x = (-1 * 2 + x * 2) + -7x + 15
-4x = (-2 + 2x) + -7x + 15

Reorder the terms:
-4x = -2 + 15 + 2x + -7x

Combine like terms: -2 + 15 = 13
-4x = 13 + 2x + -7x

Combine like terms: 2x + -7x = -5x
-4x = 13 + -5x

Solving
-4x = 13 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-4x + 5x = 13 + -5x + 5x

Combine like terms: -4x + 5x = 1x
1x = 13 + -5x + 5x

Combine like terms: -5x + 5x = 0
1x = 13 + 0
1x = 13

Divide each side by '1'.
x = 13

Simplifying
x = 13

See similar equations:

| 242=0.5(4x^2) | | 1-2(x+1)=7x-1 | | x=5y+2a | | h^2-144= | | 13-3a=8 | | 4z^4-12z^3+17Z^2-10z+2=0 | | 204=x^2+5x | | 2x^2=2+2x | | 2w^2+3w+1= | | 3x^2=5x-2 | | -.5x^2+x+24=0 | | -9x-7i= | | X^2-6=58 | | -3x^4+363=0 | | x^2-5x=4x | | 8h-10h=3h | | p^2+10p+25=0 | | h^2+7h-44=0 | | 2400=0.5(40)(15+x) | | .5x^2+x+24=0 | | 6x^2+7x+8=0 | | 400=0.5(3x) | | x+0.15x=30 | | 2x^2+5=-x | | 3(x+11)=68 | | 30-6(x-3)=9(x-5) | | 4(x-11)+6x=36 | | 3-3(x+6)=3 | | 5x+6(x-0)=11 | | 2y^3+5y^2+2y= | | 6x+6(x-4)=24 | | 20(x-3)+2x=56-2(x-4) |

Equations solver categories